Evaluation of Genotoxicity of SU-Eohyeol Pharmacopuncture Using an In Vitro Chromosome Aberration Test in Chinese Hamster Lung Cell - Jaseung Ku; Ji Hye Hwang (Korean Pharmacopuncture Institute, 2022)
Objectives: This study was conducted to evaluate the safety of SU-Eohyeol pharmacopuncture (SUEP) by assessing its potential to cause chromosomal abnormalities in Chinese hamster lung cells (CHL/IC).Methods : A dose-curve was conducted to determine the highest dose of SUEP. Doses of 10, 5, 2.5, 1.25, 0.625, and 0.313% were used, and no cytotoxicity or SUEP precipitation was observed. SUEP doses of 10, 5, and 2.5%, with positive and negative controls, were used in a chromosome aberration test.Results : In this study, the frequency of abnormal chromosomal cells in the SUEP group did not show a statistically significant difference from that of the negative control group in short-term treatments with and without metabolic activation and the continuous treatment without metabolic activation. Compared with the negative control group, the positive control group had a significantly higher frequency of cells with structural chromosomal abnormalities. This test's results satisfied all conditions for determining the results.Conclusion : SUEP did not induce chromosomal aberrations under the conditions of this study. Other toxicity evaluations, safety studies in humans, and various clinical trials are required to evaluate the safety and efficacy of SUEP.